2023
DOI: 10.3390/foods12081647
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Incorporation of Polysaccharides with Antioxidant and Antibacterial Functions to Preserve the Quality and Shelf Life of Meat Products

Abstract: Meat and meat products are susceptible to various types of natural processes such as oxidative degradation due to their high content of protein and essential amino acids. However, finding solutions to maintain the nutritional and sensory quality of meat and meat products is unavoidable. Hence, there is a pressing need to investigate alternatives to synthetic preservatives, focusing on active biomolecules of natural provenance. Polysaccharides are natural polymers of various sources that exhibit antibacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Since oxidative stress has been identified as one of the major causes of many diseases, the discovery of new effective antioxidant agents has become essential (Barouki, 2006 ; Ben Akacha, Michalak, et al., 2023 ; Ben Hsouna, Michalak, Ben Akacha, et al., 2022 ). In the present study, the antioxidant activity of different mixtures was determined, and the optimal mixture was detected based on the IC 50 values of each mixture (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since oxidative stress has been identified as one of the major causes of many diseases, the discovery of new effective antioxidant agents has become essential (Barouki, 2006 ; Ben Akacha, Michalak, et al., 2023 ; Ben Hsouna, Michalak, Ben Akacha, et al., 2022 ). In the present study, the antioxidant activity of different mixtures was determined, and the optimal mixture was detected based on the IC 50 values of each mixture (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Natural‐origin compounds have multiple advantages. The simultaneous antibacterial and antioxidant action allows for the resolution of numerous issues, including antibiotic resistance and the damaging consequences of oxidative stress (Akacha et al., 2022 ; Ben Akacha, Ben Hsouna, et al., 2023 ; Ben Akacha, Garzoli, et al., 2023 ; Ben Akacha, Michalak, et al., 2023 ; Ben Hsouna et al., 2023 ; Ben Hsouna, Hfaiedh, Ben Slima, et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important factors contributing to meat color are the myoglobin content, the chemical state of the heme structure, and the pH of the meat [68]. It has been shown that the myoglobin content depends mainly on the species and age of the animal, and that the pH of the muscle is mainly related to the biochemical state of the muscle at the time of slaughter and after the development of rigor mortis [11,69,70]. These two factors contribute to the color of the meat and the occurrence of color defects.…”
Section: ±mentioning
confidence: 99%
“…The therapeutic and beneficial health properties of plants have attracted great interest in the course of scientific developments because of their low toxicity, pharmacological effects, and economic profitability [8][9][10][11]. Most studies have focused on the benefits of plant-derived phytochemical compounds and their positive effects on human health.…”
Section: Introductionmentioning
confidence: 99%
“…The high protein content and abundant moisture and fat in meat make it highly susceptible to microbial proliferation and natural oxidation, leading to spoilage [7]. Consequently, finding solutions to maintain meat quality and sensory attributes has been a focal point for professionals and researchers in the meat industry.…”
Section: Introductionmentioning
confidence: 99%